Bring judgment day reclaiming Lead Belly's truths from Jim Crow's lies - Bernard, Sheila Curran (Cambridge University Press, 2024)
Known worldwide as Lead Belly, Huddie Ledbetter (1889-1949) is an American icon whose influence on modern music was tremendous - as was, according to legend, the temper that landed him in two of the South's most brutal prisons, while his immense talent twice won him pardons. But, as this deeply researched book shows, these stories were shaped by the white folklorists who 'discovered' Lead Belly and, along with reporters, recording executives, and radio and film producers, introduced him to audiences beyond the South. Through a revelatory examination of arrest, trial, and prison records; sharecropping reports; oral histories; newspaper articles; and more, author Sheila Curran Bernard replaces myth with fact, offering a stunning indictment of systemic racism in the Jim Crow era of the United States and the power of narrative to erase and distort the past